Forensik Video Pada CCTV Menggunakan Framework Generic Computer Forensics Investigation Model (GCFIM) - Imam Riadi; Anton Yudhana; Rachmad Very Ananda Saputra (JURIKOM (Jurnal Riset Komputer), 2023)
The level of crime recorded by CCTV (Closed Circuit Televison) cameras continues to increase, criminals who are proven to have committed certain criminal acts will be punished in accordance with statutory regulations. The problem is how a case recorded on a CCTV camera can be used as digital evidence at trial. And how to handle it if there is evidence that has been manipulated or changed by irresponsible parties to eliminate traces of digital evidence. Digital evidence is closely related to ensuring the security, privacy and integrity of data when following the stages of the forensic digital identification process. The identification model using the Generic Computer Forensic Investigation Model (GCFIM) Framework is used for the investigation stage in finding information related to video recording metadata on CCTV cameras, in order to provide structured and valid information to be accepted in court as digital evidence. The results of this study obtained information on the data testing process using the Generic Computer Forensic Investigation Model (GCFIM) framework and for the metadata analysis process using two tools, namely exiftool and mediainfo. Testing is done on the original video and tempering video. Regarding the metadata of the original video and tempering video, there is a very significant difference in the size of the original video 4.6Mb while the tempering video is 4.2Mb, the duration of the original video is 38s for the tempering video 32s and the modification date / time for the original video 2020:03:21 while the tempering video is 2022:08:04. It can be concluded that exiftool and mediainfo can be utilized to obtain metadata information from data, with the aim of strengthening digital evidence at the time of trial regarding the validity of the data